2017
DOI: 10.1111/gwat.12606
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Behavior in Methane‐Rich and Methane‐Free Groundwater in North and East Texas

Abstract: There is concern about adverse impacts of natural gas (primarily methane) production on groundwater quality; however, data on trace element concentrations are limited. The objective of this study was to compare the distribution of trace elements in groundwater samples with and without dissolved methane in aquifers overlying the Barnett Shale (Hood and Parker counties, 207 samples) and the Haynesville Shale (Panola County, 42 samples). Both shales have been subjected to intensive hydraulic fracturing for gas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…These data suggest anaerobic oxidation of methane coupled to nitrate, and potentially sulfate reduction occurred within the Parker‐Hood cluster. Darvari et al () concluded, based on the distribution of trace elements in groundwater samples within the Barnett shale footprint, that anaerobic reduction of methane in the nitrate and iron stage did occur with carbonate precipitation. It is uncertain, however, how much groundwater nitrate may have existed prior to nitrate reduction, and therefore, the contribution of nitrate reduction to dissolved nitrogen gas is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest anaerobic oxidation of methane coupled to nitrate, and potentially sulfate reduction occurred within the Parker‐Hood cluster. Darvari et al () concluded, based on the distribution of trace elements in groundwater samples within the Barnett shale footprint, that anaerobic reduction of methane in the nitrate and iron stage did occur with carbonate precipitation. It is uncertain, however, how much groundwater nitrate may have existed prior to nitrate reduction, and therefore, the contribution of nitrate reduction to dissolved nitrogen gas is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…These data suggest anaerobic oxidation of methane coupled to nitrate, and potentially sulfate reduction occurred within the Parker-Hood cluster. Darvari et al (2017) concluded, based on the distribution Figure 6. Comparison of dissolved nitrogen 15 N values and corresponding concentrations for samples collected within and near the three groundwater well clusters.…”
Section: Anaerobic Methane Oxidationmentioning
confidence: 99%
“…Shale gas operations can cause the migration of natural gas (primarily methane) from deep and intermediate nontarget zones to shallow aquifers, particularly in cases where casing/cement failures occur along well bores. ,, Fugitive gas migration into shallow aquifers can produce secondary water quality impacts associated with the mobilization of trace metals/metalloids and other redox-sensitive species (Figure ). In steady-state CH 4 -rich groundwater, trace metals/metalloids generally occur at low dissolved concentrations as a result of sulfide mineral and organic matter stability and carbonate mineral precipitation . However, in originally CH 4 -free groundwater systems, the introduction of CH 4 can lead to the mobilization of elements present in the aquifer material due to changes in physicochemical conditions.…”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 93%
“…Moreover, groundwater depletion may occur in shale gas areas where large volumes of groundwater are withdrawn for hydraulic fracturing. , The associated water table decline increases the exposure of aquifer minerals to O 2 , which diffuses through the water-unsaturated zone. These conditions may promote the release of trace metals/metalloids through sulfide mineral and organic matter oxidation. ,, …”
Section: Potential Sources Of Inorganic Contaminants In Shallow Groun...mentioning
confidence: 99%
“…Dissolved methane in drinking water is not considered a public health hazard, and it may also occur naturally in groundwater as the result of thermogenic and microbial processes (Nicot et al 2017;Moortgat et al 2018;Zhu et al 2018). Its presence in groundwater may change pH and redox conditions, causing either the release or the depletion of some trace metals depending on site conditions (Schwartz 2015;Cahill et al 2017;Darvari et al 2018). Elevated aqueous methane concentrations may also induce the separation of a gas phase, with risk of asphyxiation and explosions (Gorody 2012;Vidic et al 2013;Schwartz 2015;Schout et al 2018).…”
Section: Introductionmentioning
confidence: 99%